2017
DOI: 10.1037/aca0000061
|View full text |Cite
|
Sign up to set email alerts
|

The Green Eggs and Ham hypothesis: How constraints facilitate creativity.

Abstract: Two experiments tested the hypothesis that constraints imposed on a common writing task yield more creative outputs. In the 1st study, participants were asked to include a given noun in a 2-line rhyme for a special occasion. In the 2nd study, they generated their own nouns, which they then had to include in their rhymes. Both studies show a main effect of constraints on creativity and an interaction with order of presentation, which suggests a carryover effect: Mere practice with constraints can stimulate crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 57 publications
(55 reference statements)
3
65
0
Order By: Relevance
“…A benefit of creativity is that it can take things out of the abstract and make it more relative to real life (Herring & Hunter-Doniger, 2018). However, according to Haught-Tromp (2017), people tend to have difficulty starting work or initiating creative thought when there is an absence of any instructions, materials, directions, or examples. A foundational understanding must be present, but engineering constraints can lead to creativity.…”
Section: Fostering Creativity In the Classroommentioning
confidence: 99%
“…A benefit of creativity is that it can take things out of the abstract and make it more relative to real life (Herring & Hunter-Doniger, 2018). However, according to Haught-Tromp (2017), people tend to have difficulty starting work or initiating creative thought when there is an absence of any instructions, materials, directions, or examples. A foundational understanding must be present, but engineering constraints can lead to creativity.…”
Section: Fostering Creativity In the Classroommentioning
confidence: 99%
“…For example, a prior example may increase novelty by serving as an analogical source for new ideas (Smith & Linsey, 2011;Smith & Ward, 2012). Examples may also help to focus a search space that is otherwise very broad (Haught-Tromp, 2016;Sio et al, 2015). Additionally, novel ideas may emerge from the combination of concepts contained in prior examples with other previously known concepts (Estes & Ward, 2002).…”
mentioning
confidence: 99%
“…The most common perceived constraints come in forms like the inner critic, deficit perceptions, and fixed mindset, and inhibit the creative process. These perspectives are based in fear, shame, and cultural conditioning and can create significant barriers for individuals to reach their personal creative expression potential In contrast to the hurdle-effect of perceived constraints, and despite the fact that many associate creative expression with the fiery throws of uninhibited abandon, studies have shown that a balanced degree of actual constraints applied to a creative task can result in increased creative problem-solving and more prolific outcomes (Medeiros, 2014;Haught-Tromp, 2017). This is because a certain amount of structure or a particular prompt can help challenge and stimulate creative abilities to apply to the specific challenge at hand.…”
Section: Creative Constraintsmentioning
confidence: 99%
“…One example of this phenomenon occurred in a study where participants were provided greeting card poetry prompts. The findings demonstrated that participants who were given additional constraints (in the form of required words to include in their poems) wrote more original and intriguing poems than those who were left with utter freedom in their composition (Haught-Tromp, 2017).…”
Section: Creative Constraintsmentioning
confidence: 99%
See 1 more Smart Citation